1995
DOI: 10.1016/s0194-5998(95)70003-x
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal complications after type I thyroplasty

Abstract: Type I thyroplasty has become a primary surgical choice for voice restoration in patients with glottal incompetence. This study examines factors associated with laryngeal complications after type I thyroplasty. Ten laryngoscopic variables were analyzed from preoperative, intraoperative, and postoperative videolaryngoscopies of 51 patients undergoing 58 medialization procedures. Ten patient and operative variables were examined by medical record review. Major complications were defined as wound hemorrhage, airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
3
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 4 publications
7
82
3
4
Order By: Relevance
“…11,15,16 Although these should be taken into consideration, their incidence is low, as evidenced by our 1.4% extrusion rate and a 3% incidence of laryngeal edema. Continuous endoscopic monitoring during the surgery helps reduce misplacement of the prosthesis and under-or overmedialization.…”
Section: Discussionmentioning
confidence: 82%
“…11,15,16 Although these should be taken into consideration, their incidence is low, as evidenced by our 1.4% extrusion rate and a 3% incidence of laryngeal edema. Continuous endoscopic monitoring during the surgery helps reduce misplacement of the prosthesis and under-or overmedialization.…”
Section: Discussionmentioning
confidence: 82%
“…Extrusion occurred in an additional 7% (4/60); 3 had no change in voice after extrusion. Cotter et al 21 reported a 9% incidence of implant extrusion and attributed this to suboptimal prosthesis placement or violation of the laryngeal perichondrium and mucosa. Minor vocal hematomas were observed in 24% and resolved between 1 week and 1 month without additional intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It was thought that the smaller laryngeal size in females contributed to them being more likely to have this complication of implant extrusion. Two out of these 5 patients who had implant extrusion retained excellent glottic closure [5] . Tucker et al [9] have also reported this phenomenon in another series.…”
Section: Discussionmentioning
confidence: 93%
“…A study conducted by Cotter et al [5] described the results of 58 cord medialization procedures in 51 patients. The extrusion of implant was reported in only 5 (8.6%) cases, and interestingly, all those cases were females.…”
Section: Discussionmentioning
confidence: 99%